2017
DOI: 10.5194/acp-2017-1009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Continuous Non-Marine Inputs of Per- and Polyfluoroalkyl Substances to the High Arctic: A Multi-Decadal Temporal Record

Abstract: Abstract. Perfluoroalkyl acids (PFAAs) are persistent, bioaccumulative compounds found ubiquitously within the 10 environment. They can be formed from the atmospheric oxidation of volatile precursor compounds and undergo long-range transport through the atmosphere and ocean to remote locations. Ice caps preserve a temporal record of PFAA deposition making them useful in studying the atmospheric trends in LRT of PFAAs as well as understanding major pollutant sources and production changes over time. A 15 m ice … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 57 publications
(75 reference statements)
1
19
0
1
Order By: Relevance
“…Fluorotelomer degradation leads to deposited PFCAs with ratios that are reasonably consistent with time. Pickard et al (2018) observed that all PFCAs with carbon chain lengths ≥5 have similar deposition trends through time to the same Devon Ice Cap ice core. Ratios among PFCAs with five to eight carbons are reproduced in Figure 2b and demonstrate the difference in deposition trends for PFBA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fluorotelomer degradation leads to deposited PFCAs with ratios that are reasonably consistent with time. Pickard et al (2018) observed that all PFCAs with carbon chain lengths ≥5 have similar deposition trends through time to the same Devon Ice Cap ice core. Ratios among PFCAs with five to eight carbons are reproduced in Figure 2b and demonstrate the difference in deposition trends for PFBA.…”
Section: Resultsmentioning
confidence: 99%
“…(a) Comparison between GEOS‐Chem modeled (Thackray et al, 2020) and measured deposition ranges from 1978–2014 (Devon Ice Cap, black) and 1978–2015 (Mt. Oxford icefield, green); (b) measured molar ratios of PFCAs of different chain lengths from the Devon Ice Cap (C5 to C8 PFCA deposition from Pickard et al (2018)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6, 20 Volatile precursors can be transported long distances in the atmosphere prior to deposition in regions remote from pollution sources. 21, 22 Precursors are often not measured during standard PFAA analysis, which can result in an underestimate of human exposure because these precursors can be metabolized to terminal PFAAs in the human body. 23, 24…”
Section: Introductionmentioning
confidence: 99%
“…半球的FTOH通过LRAT-降解-沉降方式向北极传输 PFCAs的量约0.1~1 t/a [11,12] . 此外, Pickard等人 [83] [11,69] . 全球气候变暖是影响大气、海洋的PFASs传输机 制的一个重要因素 [84,85] .…”
Section: 洋流和海洋气溶胶传输是全氟辛酸盐(Perfluorooctanoate Pfo)从低纬度地区向高纬度地区传输的主要unclassified